Proses Validasi pada Pemodelan Matematis Siswa SMP (Studi Kasus: Siswa Perempuan dan Siswa Laki-Laki) - Rika Faradilla Citra Kharisma; Abdul Haris Rosyidi (MATHEdunesa, 2023)
This study aims to describe the validation process in the mathematical modeling of male and female students. The subjects of this study were male and female students at State Junior High Schools in Surabaya. Data collection procedures through the assignment of mathematical modeling problems and interviews. Data analysis refers to the validation typology of Czocher (2018). The results show that male students and female students have similarities in validating mathematical solutions obtained by repeating arithmetic operations performed previously. In addition, the two students equally succeeded in validating the real result found with consideration related to the effect of changing situation model and arithmetic operations. However, male and female students failed to generate a variety of models so that no activity emerged in generalizing the various solutions obtained. Male students are able to consider the influence of real context aspects on the solutions found, while female students are not. Female students can explain the real model that was built by mentioning the specified mathematical concepts and the reasons for using them, while male students are not.